2014
DOI: 10.1111/dech.12136
|View full text |Cite
|
Sign up to set email alerts
|

Anarchist Participatory Development: A Possible New Framework?

Abstract: This article examines the ongoing critiques and debates around the 'participatory turn' in development theory and practice and suggests anarchism as a practice-oriented theoretical framework for engaging with what participatory development ought to achieve. Explicit links are constructed between key terms in these development debates and anarchist political philosophy, and a call is made for greater attention to anarchism as a theoretical framework for radical and transformative development practice. This arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…The conclusions drawn in this paper are noteworthy for scholars within the realms of development, disaster studies, and geography, as well as policymakers interested in understanding and facilitating equitable and appropriate risk governance policies. The findings also speak to the broader and well‐established critical literature on the ‘participatory turn’ in development (for a review of these writings, see Wald, 2015).…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…The conclusions drawn in this paper are noteworthy for scholars within the realms of development, disaster studies, and geography, as well as policymakers interested in understanding and facilitating equitable and appropriate risk governance policies. The findings also speak to the broader and well‐established critical literature on the ‘participatory turn’ in development (for a review of these writings, see Wald, 2015).…”
Section: Introductionsupporting
confidence: 55%
“…15–16) as the ‘widespread risk associated with the exposure of dispersed populations to repeated or persistent hazard conditions of low or moderate intensity, often of a highly localized nature, which can lead to debilitating cumulative disaster impacts’. This was first identified through an online review of local newspapers that reported a landslide that affected 72 households in 2008 (see, for example, Wald, 2015), and was later corroborated by a scoping visit to the area in September 2012, as well as by interview and survey data.…”
Section: The Study Areamentioning
confidence: 99%
“…One crucial aspect of the R&R logs in the MID units was to encourage students to relate development readings, often from far‐away places, to their own lives, to illustrate that theories and concepts are transferrable. In the quote below, a student explains how the notion of anarchistic partnerships in rural Argentina described by Wald () resonated with her political engagement at home.
The article by Wald made me reflect on the grassroots protest movement against the Roe 8 developments in the Beeliar Wetlands in December 2016 to March 2017. Some of the anarchistic approaches explored throughout the article were definitely part of the approaches used by leaders and participants while we were protesting.
…”
Section: Embracing Emotions Through Embodied Learningmentioning
confidence: 99%
“…Navé Wald's () article introduced students to anarchistic partnerships in which the boundaries between ‘experts’ and ‘others’ are blurred, authority is understood as flat, and political culture and prefigurative politics are consciously fostered to enable radical transformation. These readings allowed the class to identify lingering binaries in participatory development and revisit Robert Chambers's () ‘uppers’ who ‘hand over the stick’ to ‘lowers’.
If you asked me several years ago what it is that developers do, I would probably have painted them in some kind of heroic light, as individuals who make deep and lasting impacts on the lives of the poor and disadvantaged.
…”
Section: Engaging With the ‘Other’ And Positionalitymentioning
confidence: 99%
See 1 more Smart Citation